Unveiling the driving role of pH on community stability and function during lignocellulose degradation in paddy soil - Wang, Yi; Chen, Yonglun; Gao, Xiuqing; Wang, Qiong; Cui, Mingyu; Zhang, Dongdong; Guo, Peng (Frontiers in Microbiology, 2024)
Crop straw, a major by-product of agricultural production, is pivotal in maintaining soil health and preserving the ecological environment. Indeed, straw incorporation is widely regarded as a sustainable approach. However, the incomplete decomposition of crop residues can hinder crop growth and elevate the vulnerability to pests and diseases, necessitating urgent investigation. Accordingly, the current study evaluates lignocellulose degradation during straw incorporation in paddy soils and the impacts of bioaugmentation and biostimulation on this process. The degradation of rice straw in paddy soils was simulated using a 28-day pot experiment. The results show that the paddy soil has high lignocellulose degradation ability, leading to a straw weight loss of > 80% within 28 days. Moreover, bioaugmentation with a lignocellulolytic microbial consortium enhances straw degradation during the initial stage (0-14 days).However, biostimulation with readily available nutrients acidifies the soil, inhibiting straw degradation and reducing microbial diversity. Furthermore, pH is a key factor influencing microbial community stability and function during lignocellulose degradation. Microbial co-occurrence network analysis revealed that microorganisms occupy ecological niches associated with different cellulose components and contribute to lignocellulose degradation. Notably, Module M2, comprised 35.14%